Manajemen Pendidikan Islam dan Implikasinya - Moh. Solehuddin (LP2M Sekolah Tinggi Agama Islam Ar-Rosyid Surabaya, 2018)
Lately there has been an interesting phenomenon, there are schools that initially experienced a setback to progress rapidly, on the other hand there are schools or madrasas that initially progressed to almost go out of business, even experiencing a sad phenomenon. In addition, there are those who initially advanced and persisted in their progress, on the contrary there were those who were originally included in the category of the proverb lâ yahya walâ yamûtu and have remained so until now. These cases were caused more by management factors than other factors, although management factors were not the sole factor independent of other factors. Therefore, to explain further what Islamic education management actually is and its implications as well as the administration, management and leadership of Islamic educators, the author will compile an article entitled